Il 'battesimo del fuoco' della direttiva sui prodotti del tabacco, tra esigenze di armonizzazione e di tutela della salute pubblica - Francesco Bestagno (European Papers, 2016)
(Series Information) European Papers - A Journal on Law and Integration, 2016 1(3), 1087-1096 | European Forum Insight of 24 October 2016 | (Table of Contents) I. Introduzione. - II. Esigenze di armonizzazione e obiettivi di politica sanitaria. - III. Il bilanciamento tra la tutela della salute e altri diritti e libertà enunciati dalla Carta dei diritti fondamentali. | (Abstract) On 4 May 2016, the ECJ delivered three judgments concerning the validity of the "Tobacco Products Directive". This article focuses on the legal basis of this controversial act and on the fundamental rights' restrictions provided for therein. As for the legal basis, the ECJ's judgments found that, in order to avoid the negative impact of divergent national legislations on the internal market, the EU is allowed to exercise its harmonizing competence in the field of public health, despite this policy being essentially reserved to the Member States. This finding was essentially based on ECJ's previous case law. With regard to the issue of the fundamental rights' restrictions raised by private parties in two of the judgments, the Court found these restrictions to be justified under the general limitation clause of art. 52 of the Charter. In more specific terms, the Court affirmed that, in the cases at hand, the EU was allowed to strike a fair balance between the need to respect fundamental rights and freedoms and the need to protect public health. This conclusion was predicated on the provisions of the TFEU and the Charter concerning the attainment of "a high level of protection" of human health. As suggested in this study, this approach of the ECJ can be read as part of a recent attitude towards referring more extensively to art. 35 of the Charter ("Health care").